Pengaruh Indeks Pembangunan Manusia (Ipm) Dan Tingkat Kemiskinan Terhadap Tingkat Pengangguran Terbuka (Tpt) Di Provinsi Dki Jakarta Tahun 2011-2020 - Gadis Puan Mahesa; Nabila Khairunnisa; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
When people who are able of working cannot find work according to their interests and skills, they have the potential to become unemployed. Unemployment is caused by decreasing job requirement, lack of experience and inadequate skills. Therefore, in this case it is necessary to expand jov vacancies, develop skills and economic growth to combat unemployment. The aim of this research is to find out how poverty and the human development index as two independent variables will influence unemployment in DKI Jakarta. This research is quantitative research using secondary data in the form of time series data for the 2011-2020 period originating from the Central Statistics Agency (BPS) of DKI Jakarta Province. The method used is multiple regression analysis using IBM SPSS 26 software. The research results show that together the HDI and Poverty Level have a significant influence on the Open Unemployment Rate in DKI Jakarta Province in the period 2011-2020.